2011
DOI: 10.1111/j.1600-0536.2010.01844.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological screening and results of patch testing among Polish apprentice hairdressers

Abstract: It is necessary to implement an educational programme for apprentice hairdressers, in order to increase their knowledge of the risk of skin damage and to promote appropriate use of protective measures, starting from the earliest stages of their training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 21 publications
(24 reference statements)
6
34
1
7
Order By: Relevance
“…In the study in Taiwan [5], 83% hairdressers had occupational dermatitis and 32% had scissor induced scars or wounds. Study in UK [6] the prevalence of hand dermatitis was 38.6% and in Poland [7] it was 43.9%. Dermatitis lesion was found 15.7% among respondents who were in this occupation for up to 5 years, 32.6% among respondents who were for 6-10 years, 27.0% among respondents who were for 11-15 years and 24.7% among respondents who were in this occupation for more than 15 years.…”
Section: Discussionmentioning
confidence: 88%
“…In the study in Taiwan [5], 83% hairdressers had occupational dermatitis and 32% had scissor induced scars or wounds. Study in UK [6] the prevalence of hand dermatitis was 38.6% and in Poland [7] it was 43.9%. Dermatitis lesion was found 15.7% among respondents who were in this occupation for up to 5 years, 32.6% among respondents who were for 6-10 years, 27.0% among respondents who were for 11-15 years and 24.7% among respondents who were in this occupation for more than 15 years.…”
Section: Discussionmentioning
confidence: 88%
“…Results of patch testing in hairdressers have been reported by a number of centres (11)(12)(13)(14)(15)(16)(17)(18)(19), and have shown differing frequencies of sensitization to a wide range of allergens. These differences may relate to different hairdressing practices in different geographical locations, as well as legislation banning the use of certain chemicals in some countries (6).…”
mentioning
confidence: 99%
“…It makes them more prone to either irritant and allergic dermatitis caused by nickel ions contained in the hairdressing tools, which may appear very early in their training, even after few months of occupational exposure [17]. Nine apprentices reported skin problems due to metal jewellery and/or clothes elements.…”
Section: Discussionmentioning
confidence: 99%
“…Krecisz et al revealed that nickel was the most frequently sensitizing skin allergen in the hairdresser apprentices group. It is thought to be rather non-occupational sensitization, resulting from skin exposure to metal objects, such as jewellery, clothing accessories and particularly from piercing [17], however the release of nickel ions from nickel-containing tools exposed to thioglycolic acid in permanent wave solutions may also contribute to the high prevalence of sensitization in this professional group [18].…”
Section: Discussionmentioning
confidence: 99%